Efficacy of Point-of-View Video Modeling: A Meta-Analysis. (November 2013) - Mason, Rose A.; Davis, Heather S.; Boles, Margot B.; Goodwyn, Fara
Point-of-view video modeling (POV), a variation of video-based modeling interventions, involves creating a video exemplar from a first-person perspective. The advantage is a significant reduction in extraneous stimuli, as well as increased efficiency in production. However, the lack of systematic analysis to evaluate differential impact on targeted outcomes for individuals with disabilities limits the identification of the population for whom POV is most appropriate, as well as the most efficacious implementation procedure. Through meta-analysis of single-subject studies using POV to improve targeted outcomes, this study identifies differential effects of participant characteristics, implementation procedures, and targeted outcomes. Results of the systematic search reveal that POV has only been implemented with individuals with developmental disabilities or an autism spectrum disorder. Analysis yielded an overall improvement rate difference (IRD) effect size of .78 (83.4% confidence interval [CI] = [.76, .80]). Furthermore, age, disability, and implementation variables moderate outcomes. Areas of future research and implications for practice are discussed.